Norm Contestation and Regional Governance: The Politics of Social Security Portability in ASEAN - Sherly Tricia Ningsih; Dwi Ardhanariswari Sundrijo (Journal of Transformative Governance and Social Justice, 2026)
This article analyzes the dynamics of conflicting norms regarding the portability of social security for migrant workers in ASEAN, particularly the political tensions between sending and receiving countries. In line with global norms, sending countries such as Indonesia and the Philippines promote portability as a fundamental right for migrant workers. Conversely, receiving countries such as Singapore and Malaysia are more cautious, viewing it as a labor issue, not a fundamental right. The research aims to analyze how these divergent interpretations shape ASEAN’s regional governance of migrant protection and to identify the underlying political and normative factors that influence the process of regionalization. Using Antje Wiener's theory of norm contestation, this study, through qualitative methods, demonstrates the gap between global expectations and normative practices in ASEAN. The findings reveal a persistent gap between global expectations and ASEAN’s normative practices. While ASEAN has made progress in formalizing cooperation, the implementation remains fragmented and state-driven, reflecting competing interests between economic pragmatism and human rights advocacy. In conclusion, the regionalization of social security is not simply a matter of applying international standards to a regional region, but rather a political negotiation shaped by competing state interests.